Structuralism - neo-structuralism and the analysis of productive development - Benavides Vindas, Shirley (2016)
The main purpose of this article is to explain, at a theoretical level, the main characteristics of structuralism and neo-structuralism, in order to assume elements that contribute to the analysis of productive development, especially when there is a clearly identified center of social economic development versus a depressed and heterogeneous periphery in the structure. This approach does not attempt to analyze particular cases of countries or regions.The evolution of structuralism (late 1940s and 1950s) to neo-structuralism (1980s) resulted in a new approach – an alternative paradigm to the neoliberal adjustment – overcoming the original structuralist paradigm from which it was inspired. This new approach included, in the analysis of economic cycles, asymmetries between centers and peripheries and the various effects of globalization resulting from open regionalism and deregulation. In addition, it included three relevant axes: economy, social equity and national autonomy, although its analytical base continued to be structuralist. In this new stage, development is proposed as a result of productive transformation with equity.Based on a structuralist and neo-structuralist theoretical approach, this paper explores the main elements of analysis that, from this perspective, can facilitate the behavior of productive sectors and the characterization of territories, providing the necessary information for the decision-making process in the design and implementation of public policies that eliminate failures in peripheral markets regarding the so-called centers and thus promote a higher level of development.